ALK1 controls hepatic vessel formation, angiodiversity, and angiocrine functions in hereditary hemorrhagic telangiectasia of the liver - Schmid, Christian David; Olsavszky, Victor; Reinhart, Manuel; Weyer, Vanessa; Trogisch, Felix; Sticht, Carsten; Winkler, Manuel; Kürschner, Sina Wietje; Hoffmann, Johannes; Ola, Roxana; Staniczek, Theresa; Heineke, Jörg; et al. (Hepatology, 2022)
Background and Aims In hereditary hemorrhagic telangiectasia (HHT), severe liver vascular malformations are associated with mutations in the Activin A Receptor-Like Type 1 (ACVRL1) gene encoding ALK1, the receptor for BMP9/BMP10, which regulates blood vessel development. Here, we established a novel HHT mouse model with exclusive liver involvement and adequate life expectancy to investigate ALK1 signaling in liver vessel formation and metabolic function. Approach and Results Liver sinusoidal endothelial cell (LSEC)-selective Cre deleter line, Stab2-iCreF3, was crossed with Acvrl1-floxed mice to generate LSEC-specific Acvrl1-deficient mice (Alk1HEC-KO). Alk1HEC-KO mice revealed hepatic vascular malformations and increased post-hepatic flow causing right ventricular volume overload. Transcriptomic analyses demonstrated induction of proangiogenic/tip cell gene sets and arterialization of hepatic vessels at the expense of LSEC and central venous identities. Loss of LSEC angiokines Wnt2, Wnt9b, and Rspo3 led to disruption of metabolic liver zonation in Alk1HEC-KO mice and in liver specimens of HHT patients. Furthermore, prion like protein doppel (Prnd) and placental growth factor (Pgf) were upregulated in Alk1HEC-KO hepatic EC representing novel candidates driving the organ-specific pathogenesis of HHT. In LSEC in vitro, stimulation or inhibition of ALK1 signaling counter-regulated Inhibitors of DNA binding (ID)1-3, known Alk1 transcriptional targets. Stimulation of ALK1 signaling and inhibition of ID1-3 function confirmed regulation of Wnt2 and Rspo3 by the BMP9/ALK1/ID axis. Conclusions Hepatic endothelial ALK1 signaling protects from development of vascular malformations preserving organ-specific endothelial differentiation and angiocrine signaling. The long-term surviving Alk1HEC-KO HHT model offers novel opportunities to develop targeted therapies for this severe disease.
Gesehen am 04.07.2022